Bio self-healing concrete using MICP by an indigenous Bacillus cereus strain isolated from Qatari soil. (18th April 2022) - Sohail, Muazzam Ghous; Disi, Zulfa Al; Zouari, Nabil; Nuaimi, Nasser Al; Kahraman, Ramazan; Gencturk, Bora; Rodrigues, Debora F.; Yildirim, Yucel
Highlights: Bacillus cereus from Qatari soils are capable of producing mineral precipitation in the same quantities as Sporosarcina pasteurii in the urea growth media. Bacillus cereus was able to fill mortar cracks from 162 µm to 670 µm wide, while the Sporosarcina pasteurii filled cracks from 200 µm to 4700 µm width. Local Bacillus cereus strain showed high urease activity and could be a viable and economical solution for the bio self-healing concrete by the bioprocess of MICP. Abstract: In this study, the self-healing process in concrete through microbial-induced calcium carbonate precipitation (MICP) performed by an adapted indigenous strain of Bacillus cereus isolated from soils in Qatar was investigated. This strain has advantage of withstanding and performing MICP in environments of 45–50 °C temperature and 80–100% relative humidity. Hence, it is considered a suitable candidate for self-healing in concrete. The performance of this new isolate was compared to that of Sporosarcina pasteurii, a well-studied strain for MICP in concrete. The strains were encapsulated in sodium alginate beads, which were then incorporated in the cement-sand mortar. It was observed that the selected local strain was able to fill cracks with widths ranging from 162 µm to 670 µm, while the Sporosarcina pasteurii strain was able to fill cracks with widths ranging from 200 µm to 4700 µm. Scanning electron microscopy (SEM) images provided evidence for the survival of the bacterial cells in the beads during the mixing of mortar and casting of the samples. The X-ray diffraction (XRD) spectra and SEM images confirmed the formation of calcium carbonates in the cracks. The local Bacillus cereus strain showed high urease activity and could be a viable and economical solution for the bio self-healing concrete through MICP where hot and humid climatic conditions are encountered.